Pengaruh Penggunaan Permainan Edukasi Ular Tangga Kebencanaan terhadap Sikap Kesiapsiagaan Gempa Bumi pada Siswa SMA Muhammadiyah 1 Bantul - Widyawati Ika Putri; Heri Puspito; Budi Santoso (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This take a look at pursuits to determine the effect of a disaster-themed snake and ladder educational game on earthquake preparedness attitudes amongst high college college students. This quasi-experimental take a look at used a non-equal manage institution design, with ninety two respondents divided into intervention and control agencies. records have been accumulated via a preparedness mind-set questionnaire and analyzed the usage of the Wilcoxon check. The consequences showed a considerable growth within the preparedness mindset score within the intervention group (p < 0.05), at the same time as no extensive trade became observed inside the manipulate organization. This suggests that the educational game effectively improves students' disaster preparedness attitudes. It is recommended that schools adopt such interactive methods to foster disaster resilience among students.